ANALYSIS OF THE WAYS OF HEATING OF THE LARGE-CAPACITY INDUSTRIAL INGOTS WITH HEIGHTENED THERMOCONTENT - V. I. Timoshpolskij; V. M. Olshanskij; I. A. Trusova; S. M. Kabishov (Литьë и металлургия)
There is made the overview of the existing ways of heating of the large-capacity industrial ingots with heightened thermocontent and first of all with non-solidified heart.